2019
DOI: 10.1108/jabes-06-2019-0053
|View full text |Cite
|
Sign up to set email alerts
|

Applying quantile regression to determine the effects of household characteristics on household saving rates in Vietnam

Abstract: Purpose The purpose of this paper is to analyse the determinants of the saving behaviour of Vietnamese households and to explore the possible heterogeneity of household saving propensities. Design/methodology/approach The authors estimate the effects of household characteristics on Vietnamese household saving rates by means of a quantile regression approach using the Vietnam Household Living Standard Survey 2010 data set. Findings The results suggest that the way household characteristics influence saving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 28 publications
(41 reference statements)
1
18
0
1
Order By: Relevance
“…Examining the different effects of urban-rural areas in China, Lugauer et al (2019) found that households in urban areas have a higher saving rate than similar households residing in rural areas. However, Hua and Erreygers (2019) documented a different finding-rural households in Vietnam tended to save more than urban households.…”
Section: Literature Reviewmentioning
confidence: 98%
See 2 more Smart Citations
“…Examining the different effects of urban-rural areas in China, Lugauer et al (2019) found that households in urban areas have a higher saving rate than similar households residing in rural areas. However, Hua and Erreygers (2019) documented a different finding-rural households in Vietnam tended to save more than urban households.…”
Section: Literature Reviewmentioning
confidence: 98%
“…In the context of ethnicity, Hua and Erreygers (2019) found that ethnicity is a crucial factor in determining the household saving rate in rural areas. Fisher and Hsu (2012) discovered that marital status is associated with a higher likelihood of saving among white households, but not among Hispanic households.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…By using structural equation modelling (SEM) for the adult population of UK, Furnham, A & Cheng, H [11], concluded that adult savings and investment have significantly strong and direct association with parental social status, educational qualifications and occupational prestige, trait conscientiousness, personal financial assessment and gender. Hua, TX & Erreygers, G [12] carried out a study in order to investigate the heterogeneity of household saving propensities in Vietnam by applying quantile regression approach. The results of the study revealed that the effects of household characteristics on saving rates vary across the quantiles in such a fashion that the influences of these characteristics on propensity to save are weaker at higher quantiles compared to lower ones.…”
Section: Literature Reviewmentioning
confidence: 99%
“…From the individual perspective, savings are essential because they generate financial safety during retirement, unexpected financial expenditures and helping in difficult situations such as disease and job losses (Iregui-Boh orquez et al, 2018). Therefore, understanding household saving behaviour, specifically its determinants, has focussed on a lot of empirical research (Hua and Erreygers, 2019).…”
Section: Introductionmentioning
confidence: 99%